Indirect employment effects of new business formation across regions: The role of local market conditions1. (9th January 2013) - Fritsch, Michael; Noseleit, Florian
Abstract We investigate the effect of local market conditions on the indirect effects of new business formation measured as their impact on employment in incumbents. Based on organizational ecology theory, we derive and test hypotheses about the magnitude of these indirect effects. The indirect effects are larger in highly populated regions, in regions with a high share of small firms, and in regions where there is high similarity between the industry structure of entries and that of the incumbents. The results show that indirect effects of new businesses emerge through competition with incumbents and underline the importance of regional conditions. We draw conclusions for policy and make suggestions for further research.